ANALISIS PROFITABILITAS PADA PT. BANK NEGARA INDONESIA 1946 TBK - SOUKOTTA, ROSITTA ANGGLIANI; MANOPPO, W. S.; KELES, DANTJE. (Sam Ratulangi University, 2016)
ABSTRACT :The company's ability to generate profits is the key to the success of the company, can be said to have a good performance, because the profit is a component of financial statements that are used as a tool to assess whether or not the company's performance. One factor that can demonstrate how the company is good or not is by analysis of financial statements. The company's ability to achieve this profit is often referred to as Profitability. The purpose of this study is to analyze and find out how the company's profits on PT. Bank Negara Indonesia Tbk in 1946, in 2013-2015 using Profitability Analysis. The results of research and discussion within a period of 3 years is the period from 2013 to 2015, that PT. Bank Negara Indonesia create a profit in 2013 amounted to 3.197% and in 2014 amounted to 3.740% and then in 2015 the bank made profits of 2.599%. Thus, each year the Bank is able to create profits in accordance with what is expected. Keywords: Analysis of profitability